The Internal Branding Implementation Towards Brand Commitment Building (Study at Universitas Pembangunan Nasional (UPN) “Veteran” East Java as the “Bela Negara” University) - S. N. Farida; N. Azizah (Future Science)
Competition in the global era requires every organization to have a competitive advantage to maintain its existence. The strategic solution in dealing with this competition is to strengthen the brand as the identity of an organization. Internal branding is the right step in strengthening an organization's brand. Seeing the growth of higher education institutions in Indonesia. Then there is a need to strengthen branding in both state and private universities. The National Development University (UPN)